HEGEMONI TIONGKOK ATAS SUNGAI MEKONG DAN PENGARUHNYA TERHADAP NEGARA DI BAGIAN HILIR: KAMBOJA, LAOS, THAILAND, VIETNAM - Irma Indrayani; Zulkarnain Zulkarnain; Dinanti Erawati (Ilmu dan Budaya, 2021)
Mekong region is a geopolitical hotspot, reflecting conflict of interests between riparian countries (China, Vietnam, Thailand, Myanmar, Laos, and Cambodia) which influence forms of complexity, perspectives and perceptions that lead to tension and conflict. Composition of forces within the Mekong refers to geographical positions that determine strategic positions. China as an upstream riparian country has a more dominant bargaining position. In trying to understand phenomenon of China hegemony, qualitative method as an approach is used through literature study. China hegemony reflects in construction of dams, formation of LMC (Lancang-Mekong Cooperation) and rejection of the MRC (Mekong River Commission).